1990
DOI: 10.1128/mcb.10.10.5455
|View full text |Cite
|
Sign up to set email alerts
|

Studies of an 800-kilobase DNA stretch of the Drosophila X chromosome: comapping of a subclass of scaffold-attached regions with sequences able to replicate autonomously in Saccharomyces cerevisiae.

Abstract: We have previously mapped scaffold-attached regions (SARs) on an 800-kilobase DNA walk from the Drosophila X chromosome. We have also previously shown that the strength of binding, i.e., the ability of SARs to bind to all nuclear scaffolds or only to a fraction of them varied from one SAR to another one. In the present study, 71 of the 85 subfragments that bind scaffolds and 38 fragments that do not bind scaffolds were tested for their ability to promote autonomous replicating sequence (ARS) activity in Saccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…These putative structural elements of chromatin have attracted considerable attention because of evidence for their involvement in the regulation of transcription, including stabilization and increased levels of transgene expression (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) [reviewed by Bode et al (4)]. The comapping of MARs and origins of replication and the functioning of MARs as ARS elements suggest a role for MARs in DNA replication (28)(29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…These putative structural elements of chromatin have attracted considerable attention because of evidence for their involvement in the regulation of transcription, including stabilization and increased levels of transgene expression (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) [reviewed by Bode et al (4)]. The comapping of MARs and origins of replication and the functioning of MARs as ARS elements suggest a role for MARs in DNA replication (28)(29)(30)(31)(32)(33)(34).…”
mentioning
confidence: 99%
“…These two neighboring attachment sites delineate a putative loop of ∼6.6 kb containing the Sh2 homolog. It should be pointed out that different functions have been suggested for strong and weak MARs (2,15) and that, in at least one case, involvement of a strong MAR in attenuating transgene silencing has been reported (9). While this is certainly an interesting issue, it is beyond the scope of this work.…”
Section: Identification and Mapping Of Mars In The Sh2/a1-homologous mentioning
confidence: 85%
“…Hence, most of the existing information on the structural organization of the genome describes individual genes and their immediate surroundings. Information on domain organization and chromosome folding at a supragenic level in animal systems is limited to only a few studies: a 320 kb continuum of the Drosophila rosy-Ace locus (13), an 800 kb region of Drosophila chromosome 1 (14,15), the 240 kb amplicon of the chinese hamster dihydrofolate reductase gene (16) and 200 kb around the mouse heavy chain IgH locus (17). The first study in plants devoted to the higher order structural organization of a large chromosomal continuum was focused on a 290 kb region around maize Adh1 (18).…”
Section: Introductionmentioning
confidence: 99%
“…S/MARs anchor chromatin onto the NM, thereby organizing the genomic DNA into topologically distinct loop domains that are important for the regulation of replication and transcription. 2 Despite numerous genomic studies, [3][4][5][6][7] no consensus S/MAR sequence has been identified so far. 8 S/MARs can be both A/T 9 or G/C rich.…”
Section: Introductionmentioning
confidence: 99%